Determinants of profitability in indonesia’s big banks: the role of capital structure, operational efficiency (bopo), and net profit margin (npm) during the 2020–2024 - Triana Yuniati; Adi Wibowo Noor Fikri; Muhammad Richo Rianto (Enrichment : Journal of Management, 2025)
This study analyzes the effect of Capital Structure (Debt to Equity Ratio/DER), Operational Efficiency (BOPO), and Net Profit Margin (NPM) on Profitability (Return on Assets/ROA) of major Indonesian banks during 2020–2024. Using a quantitative approach with secondary data from the annual financial reports of banks listed on the Indonesia Stock Exchange (IDX), the research employed multiple linear regression analysis with SPSS version 29. Classical assumption tests, including normality and heteroskedasticity, confirmed that the regression model met all statistical requirements. The findings show that DER has a negative and significant effect on ROA, indicating that higher leverage reduces profitability due to increased financial burdens. BOPO also negatively and significantly affects profitability, suggesting that inefficient cost management lowers returns. Conversely, NPM has a positive and significant effect on ROA, meaning that higher profit margins improve banks’ ability to generate returns from assets. These results are consistent with capital structure and efficiency-based profitability theories. Overall, the study highlights that maintaining an optimal capital structure, enhancing operational efficiency, and improving profit margins are crucial for sustaining profitability in Indonesia’s major banking sector. Future research should include macroeconomic factors such as inflation and exchange rate fluctuations to provide a more comprehensive analysis.